Gondwanan Inheritance on the Building of the Western Central Andes (Domeyko Range, Chile): Structural and Thermochronological Approach (U‐Pb and 40Ar/39Ar). Issue 3 (17th March 2021) - Espinoza, M.; Oliveros, V.; Vásquez, P.; Giambiagi, L.; Morgan, L.; González, R.; Solari, L.; Bechis, F.
Abstract: Tectonics inheritance controls the evolution of many orogens. To unravel the role of the Gondwanan heritage (late Paleozoic to Triassic) over the building of the Central Andes in northern Chile (Domeyko Range), we performed detrital U‐Pb zircon and 40 Ar/ 39 Ar muscovite geochronology along with structural analyses (kinematics and structural balancing). 40 Ar/ 39 Ar dating of detrital muscovite reveals contrasting cooling histories for the Paleozoic basement of Triassic rift sub‐basins, indicating that NW‐striking crustal structures segmented the Andean forearc since at least the middle Permian, likely related to an accretional fabric developed along SW Gondwana. These structures can be inferred based on scattered faults, gravimetric data, and basement age disruptions. During the Late Triassic, NS‐striking master faults and secondary NW‐ to NNW‐striking faults configured an oblique rift, primarily driven by subduction dynamics. We suggest that along SW Gondwana, the slab‐pull would have controlled the development of subduction‐related rift basins close to the trench whereas Triassic inland rifts were mainly driven by Pangea‐breakup stresses. Compressional tectonics began in the Late Cretaceous, yet the inversion of the Triassic rift would have started during the Eocene with the inception of the metallogenic‐fertile transpressional Domeyko fault system. Thus, the structural style of this range was determined by the architecture of the Triassic rift, where the inversion of deep‐seated faults accounted for west‐vergent thick‐ and thin‐skinned structures. Pre‐Andean NW‐striking structures also accommodated tectonic rotations during the Incaic orogeny (Eocene‐Oligocene) and may delimit the rupture zone of large earthquakes, suggesting an underestimated role of such ancient discontinuities in Andean neotectonics. Key Points: The synrift Domeyko Basin (Triassic) developed as an oblique rift driven by subduction and secondary far‐field Pangea‐breakup stresses During rift inversion, the metallogenic‐fertile Domeyko fault system nucleated over the former Domeyko Basin master rift faults Gondwanan NW‐striking structures controlled Paleozoic exhumation, synrift basin segmentation, and the main Domeyko Range structural style